2013
DOI: 10.1371/journal.pone.0069931
|View full text |Cite
|
Sign up to set email alerts
|

Somato-Motor Haptic Processing in Posterior Inner Perisylvian Region (SII/pIC) of the Macaque Monkey

Abstract: The posterior inner perisylvian region including the secondary somatosensory cortex (area SII) and the adjacent region of posterior insular cortex (pIC) has been implicated in haptic processing by integrating somato-motor information during hand-manipulation, both in humans and in non-human primates. However, motor-related properties during hand-manipulation are still largely unknown. To investigate a motor-related activity in the hand region of SII/pIC, two macaque monkeys were trained to perform a hand-manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 91 publications
6
27
0
Order By: Relevance
“…Fadiga et al suggested that this modulation is due to an effect along the parietal-frontal pathway. Similar interactions between motor and somatosensory signals have been shown (Ishida, Fornia, Grandi, Umilta, & Gallese, 2013;Gardner, Debowy, Ro, Ghosh, & Babu, 2002). The secondary somatosensory cortex and posterior insula cortex have reciprocal connections with the parieto-premotor grasping-related areas.…”
Section: Hand-type Neuronssupporting
confidence: 58%
See 1 more Smart Citation
“…Fadiga et al suggested that this modulation is due to an effect along the parietal-frontal pathway. Similar interactions between motor and somatosensory signals have been shown (Ishida, Fornia, Grandi, Umilta, & Gallese, 2013;Gardner, Debowy, Ro, Ghosh, & Babu, 2002). The secondary somatosensory cortex and posterior insula cortex have reciprocal connections with the parieto-premotor grasping-related areas.…”
Section: Hand-type Neuronssupporting
confidence: 58%
“…The secondary somatosensory cortex and posterior insula cortex have reciprocal connections with the parieto-premotor grasping-related areas. Neurons in these areas respond both to passive somatosensory stimulation and to the motor task (Ishida et al, 2013). This network should be involved in somatosensory control of grasping.…”
Section: Hand-type Neuronsmentioning
confidence: 99%
“…In order to assess motor-related properties in the hand region of SII/pIC, Ishida et al (2013) trained monkeys to perform a handmanipulation motor task using three different grip types (retrieving a food morsel from a groove, a cup, or a plate). A set of neurons in the SII/pIC region was only activated during active handmanipulation of the monkey.…”
Section: Somato-motor Integration In Sii/insular Of the Macaque Monkeymentioning
confidence: 99%
“…The circuit may tie social space representation and affective touch action representation. Additionally, in terms of affective touch, neurons in the hand region of SII and the adjacent posterior insular cortex (pIC) have selectivity regarding the type of hand-manipulation that represents hand motor components during grooming, handfinger exploration, and precision grasping (Ishida et al, 2013). Furthermore, the insular cortex is the center of the integration between exteroception (e.g., CT afferents) and interoception, and it interfaces with the limbic system (Mufson et al, 1981;Mufson, 1982a, 1982b;Chikama et al, 1997;Saleem et al, 2008).…”
Section: Fig 5 (A)mentioning
confidence: 99%
“…Neurones in the S2 have been found to process not just somatosensory information, but also actions in object manipulation, specifically in the stages of motor hand grasping (Ishida et al, 2013), suggesting a role in haptic integration. The S2 also appears to encode more cognitive aspects of tactile processing, such as having representations of present and past sensory information, modulations with attention, comparisons between stimuli, correlations with behavioural decisions, and tactile discrimination learning (Hsiao et al, 2002;Murray and Mishkin, 1984;Romo et al, 2002a;Romo et al, 2002b).…”
Section: Cortical Processing Of Tactile Somatosensory Inputsmentioning
confidence: 99%